Exercise before bed does not impact sleep inertia in young healthy males. (17th October 2019) - Vincent, Grace E.; Sargent, Charli; Roach, Gregory D.; Miller, Dean J.; Kovac, Katya; Scanlan, Aaron T.; Waggoner, Lauren B.; Lastella, Michele
Abstract: Sleep inertia is the transitional state marked by impaired cognitive performance and reduced vigilance upon waking. Exercising before bed may increase the amount of slow‐wave sleep within the sleep period, which has previously been associated with increased sleep inertia. Healthy males ( n  = 12) spent 3 nights in a sleep laboratory (1‐night washout period between each night) and completed one of the three conditions on each visit – no exercise, aerobic exercise (30 min cycling at 75% heart rate), and resistance exercise (six resistance exercises, three sets of 10 repetitions). The exercise conditions were completed 90 min prior to bed. Sleep was measured using polysomnography. Upon waking, participants completed five test batteries every 15 min, including the Karolinska Sleepiness Scale, a Psychomotor Vigilance Task, and the Spatial Configuration Task. Two separate linear mixed‐effects models were used to assess: (a) the impact of condition; and (b) the amount of slow‐wave sleep, on sleep inertia. There were no significant differences in sleep inertia between conditions, likely as a result of the similar sleep amount, sleep structure and time of awakening between conditions. The amount of slow‐wave sleep impacted fastest 10% reciprocal reaction time on the Psychomotor Vigilance Task only, whereby more slow‐wave sleep improved performance; however, the magnitude of this relationship was small. Results from this study suggest that exercise performed 90 min before bed does not negatively impact on sleep inertia. Future studies should investigate the impact of exercise intensity, duration and timing on sleep and subsequent sleep inertia.